2021
DOI: 10.1002/emp2.12577
|View full text |Cite
|
Sign up to set email alerts
|

Emergency physician perspectives on using telehealth with older adults during COVID‐19: A qualitative study

Abstract: Objectives Emergency medicine physicians have played a pivotal role throughout the coronavirus disease 19 (COVID‐19) pandemic through in‐person and remote management and treatment. Our primary objectives were to understand emergency medicine physicians’ experiences using telehealth throughout the pandemic, any facilitators/barriers to successful usage, lessons learned during implementation, and successful/abandoned strategies used to engage with older adults. Methods Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Data for this study were collected as part of a larger study which included PCPs, geriatricians, and emergency medicine physicians. In previously published manuscripts ( Goldberg et al, 2021 ), we reported overall findings from the larger study on physicians’ experiences using telehealth to care for older adults during the COVID-19 pandemic, as well as findings specific to emergency medicine physicians ( Davoodi et al, 2021 ). Here, we focus on experiences in primary care and geriatrics, as these office-based staff had unique experiences from hospital-based clinicians.…”
Section: Methodsmentioning
confidence: 99%
“…Data for this study were collected as part of a larger study which included PCPs, geriatricians, and emergency medicine physicians. In previously published manuscripts ( Goldberg et al, 2021 ), we reported overall findings from the larger study on physicians’ experiences using telehealth to care for older adults during the COVID-19 pandemic, as well as findings specific to emergency medicine physicians ( Davoodi et al, 2021 ). Here, we focus on experiences in primary care and geriatrics, as these office-based staff had unique experiences from hospital-based clinicians.…”
Section: Methodsmentioning
confidence: 99%
“…Telemedicine has been explored in a variety of uses, including but not limited to patient examination [7], teleconsultation [8], telesurgery [9] and medical education [10]. However, many users still do not view telemedicine as a substitute for in-person care; physicians cited limitations in diagnostic ability [11] and training [12][13][14], whereas patients cited limited interactivity and difficulty of access [15]. Advances in technology hope to address some of these barriers, with augmented reality (AR) showing considerable potential.…”
Section: Introductionmentioning
confidence: 99%
“… 4 As the pandemic progressed, more qualitative investigations were conducted exploring physician perspectives on working in subsequent waves of the pandemic, 5 , 6 the impact of COVID-19 on primary care, 7 , 8 integration of palliative medicine into intensive care units, 9 and telehealth. 10 16 …”
Section: Introductionmentioning
confidence: 99%
“…4 As the pandemic progressed, more qualitative investigations were conducted exploring physician perspectives on working in subsequent waves of the pandemic, 5,6 the impact of COVID-19 on primary care, 7,8 integration of palliative medicine into intensive care units, 9 and telehealth. [10][11][12][13][14][15][16] To inform future efforts in the COVID-19 pandemic and prepare for future crises, we must understand frontline physicians' perspectives from the first wave of the pandemic, when the least was known about this crisis. Given their central role in the healthcare system's response, further crisis management without exploration of the perspectives of frontline physicians risks missing opportunities for success as well as opportunities to anticipate and proactively address sequelae for both patients and clinicians.…”
Section: Introductionmentioning
confidence: 99%